Expected increase in staple crop imports in water-scarce countries in 2050 - Chouchane, H. (2021)
Population growth paired with growing freshwater scarcity in various parts of the world will reduce the potential of food self-sufficiency in many countries. Today, two thirds of the global population are already living in areas facing severe water scarcity at least one month of the year. This raises the importance of addressing the relationship between water availability and food import in water-scarce countries. Net import of staple crops (including cereals, roots, and tubers) is analysed in relation to water availability per capita for the period 1961–2010, considering five decadal averages. The relation found is used, together with the population growth scenarios from the United Nations, to project staple crop imports in water-scarce countries for the year 2050. As a result of population growth in water-scarce countries alone, global international trade in staple crops is projected to increase by a factor of 1.4–1.8 towards 2050 (compared to the average in 2001–2010), in order to meet the staple food needs of the 42 most water-scarce countries in the world.